Shaping the Contact between Li Metal Anode and Solid‐State Electrolytes. (24th February 2020) - Duan, Jian; Huang, Liqiang; Wang, Tengrui; Huang, Yimeng; Fu, Haoyu; Wu, Wangyan; Luo, Wei; Huang, Yunhui
Abstract: Scientific and technological interest in solid‐state Li metal batteries (SSLMBs) arises from their excellent safety and promising high energy density. However, the practical application of SSLMBs is hindered by poor contact between the Li metal anode (LMA) and solid‐state electrolytes (SSEs). To circumvent this limitation, a pattern‐guided approach that shapes the LMA/SSE contact is disclosed to offer fast Li ion conduction in the interface. A thermally‐treated copper foam is used as the lithophilic pattern to confine and guide Li for forming a tight contact with garnet‐type SSE. The contact can be easily manipulated according to the shape of lithiophilic pattern, facilitating cell assembly. The resulting Li|patterned garnet|Li symmetric cell exhibits an interfacial resistance of 9.8 Ω cm 2, which is dramatically lower than that of 998 Ω cm 2 for Li|pristine garnet|Li symmetric cell. Being used in Li–sulfur batteries, the patterned garnet effectively eliminates the polysulfide shuttle and enables stable cycling performance, showing a low capacity decay of 0.035% per cycle over 1000 cycles. The fundamental contact process of metallic anodes/SSEs is carefully investigated. This contact strategy provides a new design concept to improve the interface wettability via a lithiophilic pattern for a variety of SSEs that cannot wet with metallic anodes. Abstract : A pattern‐guided strategy is proposed to shape the contact between a Li metal anode (LMA) and garnet solid electrolytes. By engineering garnet with a lithiophilic pattern, the contact between LMA and garnet is tightly linked to the pattern shape. This interface modification effectively negates the interfacial resistance and enables long‐term stability for different types of solid‐state batteries.